Dropshipping on Sale Transactions of Sharia Economic Perspective - Khairuddin Khairuddin; Wahyu Abdul Jafar (Jurnal Madania)
The research aims to determine online sale transactions of dropshipping in within sharia economic. Therefore, the sale transactions performed are based on the sharia economic principles, share satisfaction while bringing advantage within contracting parties. This study is library research in which the documentation technique for data collection was employed. Content analysis was also used to analyze the data. The findings revealed that the implementation of sharia economic principles in online dropshipping sales transaction was performed in several ways, including not only focus on profit-oriented purposes, but also ta`abbud ila Allah (devotion to Allah), particularly. Consequently, the sale transactions should be in accordance to sharia, avoiding transaction that violates Allah’s orders. The transactions also must be freed from ribâ (usury), maysîr (gambling), and gharâr (uncertainty) elements. The parties should be careful during the transactions otherwise, they will bring mudarat (harm) and avoid maslahat (benefit). The suppliers or dropshippers are not allowed to hoard the goods (ihtikâr) that are highly needed for society.